Transtornos psiquiátricos em pacientes com hepatite C crônica e a possível associação com o uso de interferon alfa - Bruno Copio Fabregas (2010)
Psychiatric disorders are more prevalent in chronic hepatitis C patients when compared with general population. The association between interferon alpha use and depressive disorders has been reported in the literature. The objective of this work was to study psychiatric symptoms and disorders in chronic hepatitis C patients and also their possible association with interferon alpha use. Eighty one outpatients attended in a public reference service of infectious diseases in Belo Horizonte were evaluated with a psychiatric structured interview, M.I.N.I.-PLUS, and psychopathological and quality of life questionnaires and scales in the period from May 2009 to October 2010. Socio-demographic, epidemiological and clinical data were also collected and analyzed. The Beck Depression Inventory (BDI), in its full version and its primary care version (BDI-PC), the Hospital Anxiety and Depression Scale, Depression Sub-Scale (HAD-D), were investigated in psychometric and discriminative properties regarding major depression diagnosis. Variables were analyzed according to three groups of patients regarding interferon alpha exposure: Naive, Current Use and Past Use. An elevated prevalence of psychiatric disorders was found, affecting 56.8% of all patients. Major depression was the most common diagnosis, found in 22 patients (27.2%). There was association between interferon alpha current use and major depression diagnosis (p=0.027). Among seventeen patients that were in current use of interferon alpha, nine of them (53.9%) presented major depression. Major depression patients reported worse quality of life (p<0.001), fatigue (p<0.001) and worse social, psychological and occupational functioning. Other psychiatric disorders, such as dysthymic disorder, general anxiety disorder, specific phobia, obsessive compulsive disorder, post traumatic disorder and alcohol use disorder, were also associated with impairment in quality of life and functioning. BDI, BDI-PC and HAD-D showed good psychometric and discriminative properties to diagnose major depression. BDI presented a better performance with the best cutoff score of 15/16 points. In conclusion, psychiatric disorders were prevalent in the studied population. Major depression was the most frequent diagnosis and was associated with interferon alpha use. It was also a contributing factor to worse patients quality of life. Routine evaluation of depressive symptoms by the internist, including questionnaires as BDI, may be of great relevance in the assistance of chronic C hepatitis patients.